Dynamic response and performance of submarine tunnel subjected to surface explosions. (November 2021) - Yang, Guangdong; Wang, Gaohui; Fan, Yong; Deng, Ke; Lu, Wenbo; Zhao, JinShuai
Abstract: Recently, external terrorist activities have become one of the most influential events on structural safety because of the absence of proper mechanisms to detect these events. In this study, the effects of surface explosions on the dynamic response and blast resistance of a submarine tunnel are investigated by using a coupled Lagrange and Euler (CLE) method. The feasibility and accuracy of the numerical method and material models are verified against the experimental data. After that, the numerical model is utilized to investigate the dynamic behavior and damage evolution of the submarine tunnel subjected to surface explosions. The dynamic behavior of the tunnel under various detonation scenarios in terms of the explosive weight and water depth is explored. Both the localized damage mechanism and the global structural response of the tunnel are examined. Empirical formulas are proposed to predict the failure modes of tunnel. Besides, studies of tunnel protection against potential attacks by using carbon fibre reinforced polymer (CFRP) and ultra-high performance concrete (UHPC) are also discussed. Numerical results in this study provide tunnel owners and engineers with thorough and important information on the structural performance of submarine tunnels subjected to blast loads, helping them in choosing effective protection strategies for potential explosion events. Highlights: Numerical method and material models are validated against test data. Failure modes of the submarine tunnel are presented. Empirical formulas are proposed to predict the failure modes of tunnel. Mitigation effects of CFRP and UHPC on the tunnel are investigated.